Impact of euploid blastocyst developmental stage and morphological grading on pregnancy outcomes in young recurrent pregnancy loss patients: association with parental chromosomal status - Zhang, Ruixiao; Luo, Tangmiao; Cui, Chenchen; Zhang, Cuilian (Frontiers in Endocrinology, 2025)
ObjectiveThis study investigated the impact of blastocyst developmental stage and morphological grading on pregnancy outcomes following single euploid frozen-thawed blastocyst transfer (SE-FBT) in young patients with recurrent pregnancy loss (RPL) and balanced chromosomal translocations (BCTs), compared to patients with normal karyotypes.MethodsA retrospective cohort analysis was performed on 449 SE-FBT cycles (2017–2023), comprising 177 cycles from patients with BCT and 272 cycles from patients with normal karyotypes. Blastocysts were categorized according to their developmental stage (day 5 [D5] versus day 6 [D6]) and morphological grading (good versus poor). Multivariable logistic regression models were used to adjust for potential confounders.ResultsAmong BCT carriers, D5 blastocysts exhibited significantly higher clinical pregnancy rates (CPR: 83.33% vs. 62.86%; adjusted odds ratio [aOR] = 2.90, P = 0.005) and live birth rates (LBR: 75.00% vs. 51.43%; aOR = 2.6, P = 0.010) compared to D6 blastocysts, whereas morphological grading showed no significant association after adjustment. Among normokaryotypic patients, however, blastocyst morphological grading was the primary prognostic factor, with good-grade blastocysts yielding superior CPR (74.13% vs. 54.26%, aOR = 2.46, P = 0.001) and LBR (56.64% vs. 40.31%, aOR = 1.76, P = 0.039), while developmental stage had no significant effect.ConclusionsThese findings suggest that the developmental stage of the blastocyst is the primary determinant of successful outcomes in BCT-associated RPL, whereas embryo morphological grading predominantly influences pregnancy outcomes in RPL patients with normal karyotypes. These results highlight the importance of personalized embryo selection strategies based on parental chromosomal status and embryological characteristics to optimize reproductive outcomes in distinct RPL.